RVG29-modified microRNA-loaded nanoparticles improve ischemic brain injury by nasal delivery - Rubin Hao; Bixi Sun; Lihua Yang; Chun Ma; Shuling Li (Taylor & Francis Group, 2020)
Effective nose-to-brain delivery needs to be developed to treat neurodegenerative diseases. Regulating miR-124 can effectively improve the symptoms of ischemic brain injury and provide a certain protective effect from brain damage after cerebral ischemia. We used rat models of middle cerebral artery occlusion (t-MCAO) with ischemic brain injury, and we delivered RVG29-NPs-miR124 intranasally to treat neurological damage after cerebral ischemia. Rhoa and neurological scores in rats treated by intranasal administration of RVG29-PEG-PLGA/miRNA-124 were significantly lower than those in PEG-PLGA/miRNA-124 nasal administration and RVG29-PLGA/miRNA-124 nasal administration group treated rats. These results indicate that the nose-to-brain delivery of PLGA/miRNA-124 conjugated with PEG and RVG29 alleviated the symptoms of cerebral ischemia-reperfusion injury. Thus, nasal delivery of RVG29-PEG-PLGA/miRNA-124 could be a new method for treating neurodegenerative diseases.